2015 International Conference on Interactive Mobile Communication Technologies and Learning (IMCL) 2015
DOI: 10.1109/imctl.2015.7359616
|View full text |Cite
|
Sign up to set email alerts
|

Towards the gamification of inquiry-based flipped teaching of mathematics a conceptual analysis and framework

Abstract: Abstract-The paper presents a conceptual interpretation of amalgamating inquiry-based learning and the flipped classroom model with gamification / game processes as means to strengthen and improve the way Mathematics learning and teaching content, strategies and approaches are enacted in primary, secondary and tertiary education. By introducing a Personal Learning Environment (PLE) where students and teachers can create, (re)use and repurpose their own learning content (e.g. inquirybased games feedback, assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…On the other hand, the more skeptical adopters proclaim that such technologies have the potential to bring better learning outcomes only if the interventions are designed and developed under the guidelines of established learning theories and models (Mayes & de Freitas, 2007). This claim is aligned with the conclusions drawn by other researchers who suggest that, despite the increase of the digital educational tools, there is no significant impact on learners’ experience or advancement (Geiger et al., 2010; Lameras & Moumoutzis, 2015).…”
Section: Background and Related Worksupporting
confidence: 89%
“…On the other hand, the more skeptical adopters proclaim that such technologies have the potential to bring better learning outcomes only if the interventions are designed and developed under the guidelines of established learning theories and models (Mayes & de Freitas, 2007). This claim is aligned with the conclusions drawn by other researchers who suggest that, despite the increase of the digital educational tools, there is no significant impact on learners’ experience or advancement (Geiger et al., 2010; Lameras & Moumoutzis, 2015).…”
Section: Background and Related Worksupporting
confidence: 89%
“…However, issues around teachers' beliefs can be very deep-rooted and difficult to change (Donnelly et al, 2011;Ertmer & Ottenbreit-Leftwich, 2010). In the traditional conception of a classroom, the teacher commands a dominant position, is regarded as "knower", and their role is one of transmission of information (Authors, 2013a;Lameras & Moumoutzis, 2015). Often the pedagogic approaches that are complemented by technology do not fit comfortably with this teaching culture (Ertmer & Ottenbreit-Leftwich, 2010;Fullan & Langworthy, 2014;Voogt & Pelgrum, 2005).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It has been suggested that digital tools, combined with appropriate pedagogy, may have the potential to address some of the issues commonly associated with mathematics education, having the capacity to facilitate realistic, problem-solving and collaborative approaches to teaching and learning, thus providing coherency and context for the mathematics (Hoyles, 2016;ter Vrugte et al, 2015). However, many authors propose that although use of technology in the mathematics classroom is increasing, the outcomes of its utilisation do not live up to their perceived potential to enhance the learning experience (Geiger, Faragher, & Goos, 2010;Lameras & Moumoutzis, 2015;Oates, 2011;Reed, Drijvers, & Kirschner, 2010;Selwyn, 2011;Wright, 2010). In order to investigate why this may be the case, this research offers a synthesis of the general characteristics of recent, empirical research studies relating to technology usage in mathematics education.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Along similar lines, others research by the authors in [24], [1] and [25] provide an overview of the design process, but with no decision supporting guidance. It has been suggested by [26] that Unified Modeling Language (UML) can be used as a modeling tool in the gamification design process.…”
Section: Existing Design Toolsmentioning
confidence: 99%